Intra-Cadre Marriage, Religious Homogamy, and Social Sustainability: Family-Based Institutional Reproduction among Wahdah Islamiyah Cadres in Manado - Subeitan, Syahrul Mubarak; Gunawan, Edi; Bukido, Rosdalina; Abubakar, Fatum; Muhammad, Adamu Abubakar (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2026)
This study examines intra-cadre marriage among Wahdah Islamiyah cadres in Manado as a socio-legal phenomenon linking Islamic marital norms, religious homogamy, and social sustainability. The study responds to the tendency of previous discussions to portray intra-cadre marriage mainly as an expression of religious harmony, while its implications for social boundaries and institutional continuity remain insufficiently explored. Using a hermeneutic phenomenological approach, data were collected through semi-structured interviews with nine key informants, supported by observation and document analysis. The findings show that intra-cadre marriage is motivated by three interconnected objectives: implementing Islamic values in family life, strengthening da‘wah through a shared marital commitment, and fostering a rabbani generation. These objectives are sustained through the accumulation of religious capital, social closure, and the transmission of organizational values across generations. Social sustainability is reflected in family and organizational cohesion, the continuity of Islamic values, and the resilience of religious identity within a plural social environment. This study contributes to socio-legal scholarship by demonstrating that marriage within Islamic organizations functions not only as a legal and religious institution but also as a mechanism for reproducing collective identity and institutional sustainability across generations.